(untitled) (Journal of Contemporary Educational Policies and Practices, 2020)
The objective of the study is to identify the characteristics of school administrators, teachers, and students in the 4.0 educational context. The study used research method from a qualitative perspective, using a basic qualitative research model. The study participants consisted of 10 lecturers selected according to the snowball method. The study data were collected through a semi-structured interview. Content analysis techniques will be used to analyze the data. We hope that the Education 4.0 revolution can be realized in Vietnamese education system. As a result, open access, personal education, idea transformation, digital integration into education, open learning environments, lifelong learning, discovery education, and multidisciplinary education are the main components of educations 4.0. It has been found that the key qualities expected from the students of Education 4.0 are interpersonal skills, technology skills, study skills, and personal style. The main qualities expected from the teachers in educations 4.0 are technology skills, instructional skills, lifelong learning skills, and personal style. Finally, the main qualities expected from school administrators in Education 4.0 are instructional skills, technology skills, learning skills.